Pengaruh Faktor Pendidikan, Pelatihan, Motivasi dan Pengalaman Kerja terhadap Kinerja Kepala Desa (Studi pada Kepala Desa di Kecamatan Pakis dan Tumpang Kabupaten Malang) - Warsito, Bambang (Universitas Brawijaya, Indonesia, 2008)
This research aim to know and analysis influence of education factor, training, job experience and motivation to performance lead countryside (study at Head Countryside in District of Fern and Join with others unlucky Sub-Province). This research is conducted by in Unlucky Sub-Province, taken sample counted 30 responders of head Countryside in District of Fern and Join With Others Unlucky Sub-Province. To test influence of education factor, training, job experience and motivation to performance lead countryside used by analysis of regression doubled liniear. Result analysis Doubled linear regression show result of R2 equal to 0.696 or equal to 69,6%. This result indicate that counted 69,6% variable of dependent can be explained by independent variable. While counted 30.4% ad for explained by other variable which do not the included in this research Result of Uji-7 show that any free variables that is education, training. motivation, and job experience, by partial have an effect on isnt it to performance Lead Countryside (in] District of Fern and Join With Others Unlucky Sub-Province. Variable Experience by partial is most dominant variable (of) influence of to performance of countryside, thereby accepted (both/ second) hypothesis. Experience factor have an effect on dominant to performance lead Countryside. This matter is proved by level of coefficient of regression discipline variable work bigger than coefficient of regression other variable (0,696 0,639 0,574 0,242). Thereby, hypothesis expressing that job experience have an effect on dominant to performance lead countryside have proven statistically.